Evaluation of the Effect of Breed and Line on Slaughter Value and Quality of Lamb Meat - Janoš, Tomáš; Filipčík, Radek; Hošek, Martin; Dračková, Eliška; Kamanová, Vendula (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2019)
The aim of our experiment was to evaluate to what degree carcass value and quality of lamb meat are effected by selected breeds (Zwartbles, Suffolk, Romney Marsh) and lines (Zbyšek, Ztepl, Záblesk, Ewebank Armani, President, Romeo, Avatar). Suffolk breed rams were found to have (p ≤ 0.05) the lowest weight at slaughter (37.47 ± 4.10 kg) and also carcass weight (15.23 ± 1.78 kg). Romney Marsh‘s carcasses had a significantly higher degree of fat cover (3.6 ± 0.4), kidney fat ratio was 0.78 ± 0.17 % and the percentage of fat from the right leg was 2.50 ± 0.61 %. The conclusively (p ≤ 0.01) highest ratio of the right leg was recorded in the Suffolk breed (17.00 ± 0.79 %). The highest ratio of the leg of carcass among the lines was found in the President line (17.53 ± 0.66 %). Meat of the Suffolk line had the significantly (p ≤ 0.01) highest ratio of dry matter, intramuscular fat, protein and ash. Among the lines, this trend was similar in favor of the Suffolk’s line. The Zwartbles breed had the lowest (p ≤ 0.01) ratio of fat and dry matter in the meat. The value of pH, lightness (L* = 51.55 ± 1.66) and color spectrum b* (13.12 ± 0.46) of meat was conclusively (p ≤ 0.01) the highest in the Zwartbles breed, while the redness indicator (7.56 ± 1.45) was conclusively the lowest for this breed. Statistically (p ≤ 0.01), the meat of the Suffolk breed had the most potent red color (a* = 11.87 ± 1.24) and the highest water‑holding capacity (81.57 ± 1.87).